Linkage Between Site Features and Soil Characteristics Within a Mediterranean Volcanic Area - Panico, Speranza Claudia; Memoli, Valeria; Santorufo, Lucia; Esposito, Francesco; De Marco, Anna; Barile, Rossella; Maisto, Giulia (Frontiers in Forests and Global Change, 2021)
Altitude, exposure and plant cover may have a signiﬁcant impact on soil system, affecting its abiotic characteristics and, in turns, soil microbial composition and activity. In Mediterranean area, the relationships among environmental features and soil characteristics are still scarcely investigated. The present study aimed to evaluate the effects of altitude, slope exposure and plant cover on soil abiotic characteristics and the responses of soil microbial community. Surface soil was sampled at 32 field points of the Vesuvius Mountain (Southern Italy) at two slope exposures (North and South), two altitudes (600 and 900 m a.s.l), and under two different plant covers (pines and shrubs) and it was analysed for soil abiotic and biotic characteristics. The results showed that soil characteristics mainly differed according to site altitude, but some characteristics also changed according to site exposure and plant cover. The soil organic carbon (Corg) showed significant high values at low altitude, south exposure and under pines and played a role in influencing soil microbial community. In soil covered by pines, the greatest soil Corg amount matched with the highest values of C/N ratio and fungal biomass. Finally, high Corg and water availability signiﬁcantly enhanced the microbial activities.